Silicon quantum processor with robust long-distance qubit couplings - Guilherme Tosi (Nature Portfolio, 2017)
Quantum computers will require a large network of coherent qubits, connected in a noise-resilient way. Tosi et al. present a design for a quantum processor based on electron-nuclear spins in silicon, with electrical control and coupling schemes that simplify qubit fabrication and operation.